2022
DOI: 10.1038/s41467-022-30069-1
|View full text |Cite
|
Sign up to set email alerts
|

Transition from predictable to variable motor cortex and striatal ensemble patterning during behavioral exploration

Abstract: Animals can capitalize on invariance in the environment by learning and automating highly consistent actions; however, they must also remain flexible and adapt to environmental changes. It remains unclear how primary motor cortex (M1) can drive precise movements, yet also support behavioral exploration when faced with consistent errors. Using a reach-to-grasp task in rats, along with simultaneous electrophysiological monitoring in M1 and dorsolateral striatum (DLS), we find that behavioral exploration to overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…We found inter-individual variability within animals, and we found that LFO activity emerged in animals that were able to gain expertise in the task within five days. Previous reports indicate that slow improvements in accuracy can continue to occur with extended practice in rodent reach-to-grasp task (Lemke et al, 2019) and behavioral exploration phase can vary between animals when the target location is switched in this reaching task (Kondapavulur et al, 2022). Our paradigm involved training for contiguous five days and we observed emergent LFO trends in animals that gained proficiency in the task.…”
Section: Discussionmentioning
confidence: 67%
“…We found inter-individual variability within animals, and we found that LFO activity emerged in animals that were able to gain expertise in the task within five days. Previous reports indicate that slow improvements in accuracy can continue to occur with extended practice in rodent reach-to-grasp task (Lemke et al, 2019) and behavioral exploration phase can vary between animals when the target location is switched in this reaching task (Kondapavulur et al, 2022). Our paradigm involved training for contiguous five days and we observed emergent LFO trends in animals that gained proficiency in the task.…”
Section: Discussionmentioning
confidence: 67%
“…To directly compare the neural substrates of flexible and automatic motor sequence execution, we designed a discrete sequence production task for rats based on similar paradigms in humans and non-human primates (NHPs) 22,57,63 . Importantly, we wanted our paradigm to distinguish motor automaticity from habit formation 11,12 , two independent processes that can occur alongside each other and that may involve some of the same neural substrates 11,64,65 . Thus, we designed our task to ensure that rats achieve automaticity on a motor sequence without developing it into a habit.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, we wanted our paradigm to distinguish motor automaticity from habit formation 11,12 , two independent processes that can occur alongside each other and that may involve some of the same neural substrates 11,127,128 . Thus, we designed our task to ensure that rats achieve automaticity on a motor sequence without developing it into a habit.…”
Section: Methodsmentioning
confidence: 99%
“…The dynamical system approach faces the same challenges as the representational model: rotations exhibit diverse shapes and occur during various movement types, contexts, and behaviors (see Introduction), which are difficult to explain by either model or their combination [16,17,29,51].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the following areas have been studied: primary motor cortex ('hand knob' area) [45,46] and left superior temporal gyrus (STG) [47] in individuals with movement impairment. In rodents, jPCA method has been applied to the data collected in the following areas: auditory and motor cortices of mice [48][49][50] and primary motor cortex and dorsolateral striatum (DLS) of rats [51]. Furthermore, jPCA method has been applied across different motor tasks and contexts.…”
mentioning
confidence: 99%